How is the care provided by physicians to patients with dementia in Primary Care? (Research, Society and Development, 2022)
Introduction: the incidence of neurogenerative diseases has been progressively increasing as a result of population aging. Thus, it is essential to establish cognitive screening protocols to identify cognitive and behavioral changes, early diagnosis and immediate treatment, in monitoring the elderly, especially in Primary Health Care services. Objectives: To describe the attitudes and professional profile of doctors in the care of patients with dementia, in the city of São Caetano do Sul, in primary care. Method: quantitative, cross-sectional, descriptive study, with a non-probabilistic sample, collected for convenience, through the application of the instrument “Atenció Sanitària de Les Demències: la visió de L'Atenció Primarià – for physicians – Brazilian version”, to healthcare physicians Primary Care in São Caetano do Sul. Results: there was 100% participation in Primary Care, totaling 28 doctors, 50% of which were female. Participants have, on average, 82 months of experience in Primary Care. It was observed that 82.6% reported that they more frequently diagnose users with dementia in a moderate condition; 68.2% reported difficulties in clinically monitoring users with severe dementia and 87% mentioned that they refer users to neurologists for diagnosis. Part of physicians (39.1%) reported referring more than 75% of patients with dementia to referral services. Even though the entire sample understands the importance and need, 34.8% have not yet taken an update on the topic of dementia. The main difficulties reported by physicians are related to drug prescription, the need for frequent visits, and the complexity of care. Conclusion: There were gaps in the identification of dementia, as well as in the adequate clinical monitoring of patients, generating unqualified directions for secondary care, reducing the resolution of primary care for such a demand. The urgent need to update physicians was evident, with a view to improving the quality of care provided.